OPTIMAL CONTROL OF INFLUENZA A DYNAMICS IN THE EMERGENCE OF A TWO STRAIN - Nainggolan, Jonner (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
This paper examines the influenza spread model by considering subpopulation, vaccination, resistance to analgesic/antipyretic drugs + nasal decongestants. Based on the studied model are determined, non-endemic, endemic stability points and the basic reproduction number. In the model studied, control is given in an effort to prevent contact of individuals infected with influenza and susceptible (u1), and control treatment for infected individuals in an effort to accelerate the recovery of infected individuals (u2). In the numerical simulation, using the control u1 the number of infected individuals subpopulation decreased compared to that without control. The number of individual recovered subpopulations using the u2 control increased more than that without the control.